Test of an amorphous silicon detector in medical proton beams - Martišíková, Mária; Hesse, B. M.; Nairz, O.; Jäkel, Oliver (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2011)
Ion beam radiation therapy for cancer treatment allows for improved dose confinement to the target in comparison with the standard radiation therapy using high energy photons. Dose delivery to the patient using focused ion beam scanning over the target volume is going to be increasingly used in the upcoming years. The high precision of the dose delivery achieved in this way has to be met by practical methods for beam monitoring with sufficient spatial resolution in two dimensions. Flat panel detectors, used for photon portal imaging at the newest medical linear accelerators, are an interesting candidate for this purpose. Initial detector tests presented here were performed using proton beams with the highest available energy. The investigations include measurements of beam profiles at different beam intensities and for different beam width, as well as the signal linearity. Radiation damage was also investigated. The obtained results show that the detector is a promising candidate to be used in the therapeutic proton beams.